Repositioning for pressure injury prevention in adults: An abridged Cochrane systematic review and meta-analysis. (August 2021) - Gillespie, Brigid M; Walker, Rachel M; Latimer, Sharon L; Thalib, Lukman; Whitty, Jennifer A; McInnes, Elizabeth; Lockwood, Ishtar; Chaboyer, Wendy P
Abstract: Background: A pressure injury is an area of localised damage to the skin and underlying tissues. Patient repositioning is an important prevention strategy, as those with limited mobility are at increased risk of developing pressure injury. Objectives: To assess the clinical and cost-effectiveness of repositioning schedules on the prevention of pressure injury in adults. Design: Systematic review and meta-analysis. Data sources: The Cochrane Wounds Specialised Register; the Cochrane Central Register of Controlled Trials; MEDLINE (Ovid); Embase (Ovid) and Cumulative Index of Nursing and Allied Health Literature Plus (EBSCO) were searched in February 2019. No restrictions were applied to language or date of publication. Review methods: Studies were eligible if they were randomised controlled trials including cluster trials, published or unpublished, and undertaken in any healthcare setting that assessed the clinical and/or cost effectiveness of repositioning schedules for prevention of pressure injury in adults. Methodological quality of the studies was independently assessed by three authors. Heterogeneity between studies was assessed using the I 2 statistic, and the pooled risk ratios along with their 95% confidence intervals were estimated using either fixed and random effects models, as indicated. Grading of Recommendations Assessment, Development and Evaluation was used to appraise the certainty of evidence. Results: Eight eligible trials involving 3, 941 participants published between 2004 and 2018 were identified. Trials compared either different repositioning frequencies or positioning regimens. Three trials (1074 participants) compared 2-hourly with 4-hourly repositioning (risk ratio 1.06, 95% confidence interval 0.80 to 1.41; I 2 = 45%). Two other trials (252 participants) compared a 30-degree tilt with a 90-degree tilt (risk ratio0.62, 95% confidence interval 0.10 to 3.97; I 2 = 69%). Only two trials included economic analyses, both amongst nursing home residents. One study estimated the costs of repositioning to be Canadian dollars 11.05 and Canadian dollars 16.74 less per resident per day for the 3-hourly or 4-hourly regimens, respectively, when compared to 2-hourly regimen. The second study reported 3-hourly repositioning using a 30-degree tilt to cost €46.50 (95% confidence interval €1.25 to €74.60) less per patient in nursing time compared with 6-hourly repositioning with a 90-degree lateral rotation. Conclusion: It remains unclear which repositioning frequencies or positions are most effective in preventing pressure injury in adults. There is limited evidence to support the cost effectiveness of repositioning frequencies and positions. Registration: Cochrane protocol published in 2012.